The British Academy Brian Barry Prize Essay: An Exit, Voice and Loyalty Model of Politics. Issue 4 (14th March 2017) - Clark, William Roberts; Golder, Matt; Golder, Sona N.
Abstract : Political scientists typically develop different models to examine distinct political phenomena such as lobbying, protests, elections and conflict. These specific models can provide important insights into a particular event, process or outcome of interest. This article takes a different tack. Rather than focus on the specificities of a given political phenomenon, this study constructs a model that captures the key elements common to most political situations. This model represents a reformulation and extension of Albert Hirschman's famous Exit, Voice and Loyalty framework. To highlight the value that comes from focusing on the commonalities that exist across apparently disparate political phenomena, the article applies the model to several issues in the democratization literature related to modernization theory, the political resource curse, inequality, foreign aid and economic performance.